Circumstellar Envelopes of Stars on the Asymptotic Giant Branch:The determination of gas mass-loss rates, identification of molecules and detection of dust - Alm, Marcus; Angerd, Gabriel; Lundberg, Tomas; Wölfinger, Alexander; Oleszko, Sebastian (My University, 2019)
Using data observed in Band 6 (211-275 GHz) and Band 7 (275-373 GHz) with the interferometer ACA (part of ALMA) from the DEATHSTAR project [1] we have analysed the CSEs of 5 AGB stars; three carbon-rich (Y Hya, U Hya and R For) and two oxygen-rich (R Hya and R Crt). The analysis was comprised of three main areas: determining the gas mass-loss rates, ˙M , identifying molecules and investigating the presence of dust, where the analysis of M was the most extensive. Using the CO lines J = 2 ! 1 and J = 3 ! 2 we determined ˙M with an equation from Ramstedt et al. 2008 [2] based on CO radiative transfer, as well as the expansion velocities of the CSEs. All calculated values of ˙M , ranging 2.2-22 · 10−7 M yr−1 (+79%/ − 66%), were within the equations stated error margin of a factor of three[2] and consistently higher, compared to values in the literature obtained with CO radiative transfer modelling[3, 4]. Due to the equation used for ˙M being based on single-dish telescopes, conversions for our data had to be made. Therefore, a systematic error in the conversion could account for the higher values. Furthermore, the expansion velocities were significantly higher than those in the literature[4] for all stars except Y Hya. However, the data used by us had a higher signal to noise ratio and overall lower uncertainty in comparison[5], indicating that our values may be more accurate. All molecules identified from the frequency spectra in Band 6 (215.4 - 217.4, 217.3-219.3, 230.2-231.2, 231.1-233.1 GHz) and Band 7 (330.3-331.3, 331.3-333.3, 342.5-344.5, 345.1-346.1 GHz), 15 in total with 11 in the carbon stars and 10 in the oxygen stars, were common for the respective spectral type except the recently (2016) discovered AlO [6], which was identified in R Crt. The spectral index, , was calculated from the flux in continuum emission in Band 6 (224.3-241.9 GHz) and band 7 (338.2-354.0 GHz). The temperature was calculated for the stars with 2 (Y Hya and R Crt) and agreed with the temperatures in the literature [3, 4]. For the stars with 6= 2 (U Hya, R For and R Hya) the dust mass, MD, and the dust mass-loss rate, ˙MD, was calculated with an assumed dust temperature of Tdust =100 K if the measured flux was 10% higher than expected (R For and R Hya), giving the uncertain values (due to Tdust having an exponential relation) MD = 10−5M for both stars and ˙MD = 10−8M yr−1 and ˙MD = 10−7M yr−1 for R For and R Hya respectively.
Keywords: Fysik; Astronomi, astrofysik och kosmologi; Physical Sciences; Astronomy, Astrophysics and Cosmology